2015
DOI: 10.1134/s0021364015180034
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced dynamics and femtosecond excitation of phonon modes in ferroelectric semiconductor Sn2P2S6

Abstract: The ultrafast dynamics of electrons and phonons excited by femtosecond light pulses in ferroelectric semiconductor Sn 2 P 2 S 6 is investigated using the optical pump-probe technique. It is demonstrated that a soft mode can be excited in this ferroelectric in the vicinity of the phase transition initiated by laser radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
(37 reference statements)
0
6
0
3
Order By: Relevance
“…Attempts at all‐optical switching of the order parameter in ferroics have been presented in a number of publications. [ 5–7 ] For magnetic materials, it was shown that ultrafast all‐optical switching of magnetization is possible using femtosecond laser pulses. [ 7 ] At the same time, a similar ultrafast control of the ferroelectric order parameter has not yet been achieved.…”
Section: Figurementioning
confidence: 99%
“…Attempts at all‐optical switching of the order parameter in ferroics have been presented in a number of publications. [ 5–7 ] For magnetic materials, it was shown that ultrafast all‐optical switching of magnetization is possible using femtosecond laser pulses. [ 7 ] At the same time, a similar ultrafast control of the ferroelectric order parameter has not yet been achieved.…”
Section: Figurementioning
confidence: 99%
“…Ранее нами было установлено, что в этом материале время термализации τ 1 = 1.62 ± 0.03 ps [13]. С учетом этого в данной работе было установлено, что характерное время рекомбинации электронов из зоны проводимости в валентную зону τ 2 ∼ 620 ps.…”
Section: фотоиндуцированная динамика генерации второй оптической гармunclassified
“…Ранее [13] нами была продемонстрирована возмож-ность возбуждения мягкой фононной моды в кристал-ле сегнетоэлектрика-полупроводника Sn 2 P 2 S 6 (SPS) под действием фемтосекундного лазерного импульса. Это может свидетельствовать о возможности влияния света на сегнетоэлектрический параметр порядка и, по ана-логии с магнитными материалами, может стать первым шагом на пути к полному оптическому переключению сегнетоэлектрической поляризации.…”
Section: Introductionunclassified
“…Optical excitations can be also used for polarization switching. The idea [12] is to use coherent phonons excitation by impulsive Raman scattering analogously to magnon excitation in magnetic materials [13]. However, contrary to magnetization switching, the polarization switching has not achieved in this way in spite of extensive studies [14][15][16].…”
Section: Introductionmentioning
confidence: 99%